Phelan-McDermid Syndrome in Spanish children: gastrointestinal manifestations in relation to nutritional intake - Carrera-Juliá, Sandra; Vega-Bello, María Jesús; Gómez-Taylor, Bárbara; Drehmer, Eraci; Navarro, Mari Ángeles; Moreno, Mari Luz (Frontiers in Nutrition, 2025)
BackgroundPhelan-McDermid Syndrome (PMS) is a rare genetic disorder associated with neurodevelopmental delay, speech impairment, and frequent gastrointestinal symptoms. While dietary management may influence health outcomes in rare diseases, there is limited data on the nutritional profile of PMS patients. This study aimed to evaluate dietary intake, digestive symptoms, and growth parameters in Spanish children with PMS.MethodsA cross-sectional descriptive study was conducted involving 37 Spanish children (aged 1–18 years) diagnosed with PMS. Digestive symptoms and food intolerances were collected through patient histories. Dietary intake was assessed using a 7-day food diary and a Food Frequency Questionnaire, analyzed with Easy Diet® software. Nutritional adequacy was evaluated against national (SENC, FESNAD) and international (WHO) recommendations. Anthropometric measurements (weight, height and BMI) were taken according to ISAK standards.ResultsMost participants (75.7%) presented digestive symptoms, with significant gender differences observed in swallowing difficulties, reflux, and gases. Diet analysis revealed significant deficiencies in energy, fiber, calcium, iron, vitamins D and E and excesses in simple sugars, protein, saturated fats, cholesterol, and certain vitamins and minerals. Anthropometric data showed mean weight, height, and BMI around the 50th percentile and mean WHO z-scores were close to the reference median (WAZ = 0.03, HAZ = −0.15, BAZ = 0.16), supporting an overall adequate growth pattern.ConclusionGiven the gastrointestinal symptoms observed in Spanish children with PMS, specialized nutritional supervision is required, whereby nutrition professionals educate children, parents, and caregivers on strategies such as increasing fibre and calcium/vitamin D intake, with supplementation when required, and limiting simple sugars, saturated fats, and processed meats. These interventions aim to address the identified imbalances and enhance the quality of life of individuals with PMS.